"Meni je ta moja pot kot dnevna soba" - Bajič, Blaž (Etnolog. Nova vrsta (Ljubljana), 2016)
The article addresses joggers and "their" routes in and out of Ljubljana, emphasizing the difference between the city and nature that is of essential importance to many joggers. They often do not agree on the contents of these two domains, but they do not question their different nature, which they take as a given. Their practices and narratives about nature emerge in the context of the historically longer production and ideology of nature and jogging in late capitalism. Jogging along chosen routes provides an authentic, rich sensorial experience or transition from the city "back to nature", but behind their experiences is a complex socio-economic network on which contemporary jogging depends.
Keywords: urbana antropologija; sport; šport; recreation; rekreacija; tekači; navade; oblačilna kultura; športna obutev; Ljubljana